L–Thyroxine induced hyperthyroidism effect on Testicular endoplasmic reticulum stress and Perk–mediated Nrf2/HO–1 signaling axis of rats - Arkalı, Gözde; Özer Kaya, Şeyma; Çeribaşı, Songül; Güler Ekmen, Edanur; Aksakal, Mesut; Çay, Mehmet (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
The effect of thyroid gland on the male reproductive system (neonatal–prepubertal and adult periods) has been investigated for many years. Hypertyhroidism may cause male infertility by effecting spermatological parameters such as loss of motility and decreased of sperm concentration. However, the mechanisms of male infertility caused by hyperthyroidism are still not fully explained. The aim of this study was to investigate the effect of hyperthyroidism on testicular endoplasmic reticulum stress and the protein kinase RNA–like endoplasmic reticulum kinase (PERK) mediated antioxidant pathway in adult male rats. 24 Sprague Dawley adult male rats were used. Rats were divided into two groups: control group (received intraperitoneal injections of saline solution 1 mL·day-1 for 8 week) and hyperthyroidism group (received intraperitoneal injections of l–thyroxine 0,3 mg·kg-1·mL-1·day-1 for 8 week). The serum free triiodothyronine (fT3) (P<0.01) and free thyroxine (fT4) (P<0.05) levels were increased, thyroid stimulating hormone (TSH) level (P<0.01) and final body weight (P<0.001) were decreased in the hyperthyroid groups. It was determined that tubulus seminiferus contortus diameters, germinal cell thicknesses, johnsen testicular score values significantly decreased in the hyperthyroid group (P<0.001). It was determined that it had a negative effect on reproductive organs weight and spermatological parameters. As per our results, hyperthyroidism significantly increased malondialdehyde level (P<0.01), glutathione level (P<0.001), glutathione peroxidase enzyme activity (P<0.001), PERK, GRP78 (P<0.01), ATF4 (P<0.05), Nrf2, HO–1 (P<0.05) protein expression levels and significantly decreased catalase activity (P<0.05). These results showed that increased thyroid hormones levels may be a negative factor in terms of testicular physiology as it causes endoplasmic reticulum stress in the testes, and PERK mediated antioxidant response may play an important role in testicular tissue in hyperthyroidism.